2013
DOI: 10.1152/ajpheart.00077.2013
|View full text |Cite
|
Sign up to set email alerts
|

The role of mitochondrial bioenergetics and reactive oxygen species in coronary collateral growth

Abstract: Coronary collateral growth is a process involving coordination between growth factors expressed in response to ischemia and mechanical forces. Underlying this response is proliferation of vascular smooth muscle and endothelial cells, resulting in an enlargement in the caliber of arterial-arterial anastomoses, i.e., a collateral vessel, sometimes as much as an order of magnitude. An integral element of this cell proliferation is the process known as phenotypic switching in which cells of a particular phenotype,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…In isolated brain mitochondria, cultured neurons, astroglia and cerebral vascular endothelium, and intact cerebral vascular endothelium and VSM, the agent BMS-191095 causes mitochondrial depolarization without ROS production and promotes diverse cellular responses such as pre-/post-conditioning and VSM relaxation; thus, mitochondrial depolarization alone is sufficient to activate distinct cellular signaling pathways (12,15,64,86,88,89). Our findings with BMS-191095 are supported by results from other laboratories (126,143,144) and by other experimental approaches in our laboratory (41).…”
Section: Mitochondrial Depolarization and Related Signaling Eventssupporting
confidence: 85%
See 1 more Smart Citation
“…In isolated brain mitochondria, cultured neurons, astroglia and cerebral vascular endothelium, and intact cerebral vascular endothelium and VSM, the agent BMS-191095 causes mitochondrial depolarization without ROS production and promotes diverse cellular responses such as pre-/post-conditioning and VSM relaxation; thus, mitochondrial depolarization alone is sufficient to activate distinct cellular signaling pathways (12,15,64,86,88,89). Our findings with BMS-191095 are supported by results from other laboratories (126,143,144) and by other experimental approaches in our laboratory (41).…”
Section: Mitochondrial Depolarization and Related Signaling Eventssupporting
confidence: 85%
“…It also has been reported that a genetic deficiency of MnSOD in mice increases basal superoxide levels in cerebral arteries and aorta (10). Moreover, Pung et al have shown that chronic inhibition of Complex I by rotenone blocks ischemia induced collateral artery growth in the coronary circulation via activation of adenosine monophosphate-activated kinase and the subsequent inhibition of mechanistic target of rapamycin (mTOR) and p70 ribosomal S6 kinase (126). Higher levels of cellular ROS, such as occurs during injury and disease, can lead to cell death via both mitochondrial-and nonmitochondrial-mediated pathways, especially in metabolically compromised conditions (6,23,29,38,93,138).…”
Section: Mitochondrial Energetics and Reactive Oxygen Species Productionmentioning
confidence: 99%
“…It has been found that endothelial cell dysfunction affects the diffusion rate of oxygen across the arteriolar vessel wall [49,50]; however, these observations require further discussion. In endothelial cells, due in larger part to the unique nature of endothelium's limited metabolic demands, mtROS primarily play a prominent role as cell-signaling molecules [51,52]. Vascular endothelial cells overwhelmingly rely on glycolysis rather than the TCA cycle for cellular ATP needs [53,54].…”
Section: Mitochondrial Oxidative Stressmentioning
confidence: 99%
“…It also has been reported that a genetic deficiency of MnSOD in mice increases basal superoxide levels in cerebral arteries and aorta [10]. Additionally, Chilian et al have shown that chronic inhibition of Complex I by rotenone blocks ischemia induced collateral artery growth in the coronary circulation via activation of adenosine monophosphate activated kinase, and the subsequent inhibition of mTOR and p70 ribosomal S6 kinase [119]. Higher levels of cellular ROS, such as occurs during injury, can lead to cell death via both mitochondrial- and non-mitochondrial-pathways, especially in metabolically compromised conditions [57,89].…”
Section: Ros Production and Release By Mitochondriamentioning
confidence: 99%